Equity and Efficiency Measures of Tax-Transfer Systems: Some Evidence for New Zealand - John Creedy; Jamas Enright; Norman Gemmell; Nick McNabb (New Zealand Government, The Treasury, 2008)
The redistributive and efficiency aspects of personal taxes are of particular interest to both economists and governments designing tax reforms. Traditionally however, the numerous analytical tools available to calculate distributional and efficiency effects of taxes and transfers are not widely used in tax policy advice. This partly reflects the computational complexities involved in calculating some of those measures and the need for simplicity, and transparency of underlying assumptions, when presenting policy advice. This paper makes two contributions to the analysis of the equity and efficiency effects of tax policy. Firstly, it applies the methodologies proposed by economists to measure equity and efficiency outcomes of taxes to provide some evidence for the New Zealand income tax and transfer system. This makes use of Treasury's microsimulation model, TaxWell. Secondly, the paper examines a database of low-income New Zealand taxpayers. A decomposition by individual and household characteristics shows that different groups of low income taxpayers can be affected quite differently by various aspects of the tax/transfer system. In particular, tax-free zones do not appear well targeted to help those most in need.
Keywords: H23; H24; 330; Personal Income Taxes; Equity; Redistribution; Transfers; Tax Efficiency; Einkommensteuer; Steuerinzidenz; Gerechtigkeit; Besteuerungsverfahren; Effizienz; Neuseeland